Protection of human rights in Southeast Asia with special reference to the Rohingya in Myanmar: a critical study of the effect of ASEAN’s policy and action on ASEAN Intergovernmental Commission on Human Rights (AICHR) - Rachminawati, Rachminawati; Mokhtar, Khairil Azmin (Universitas Padjadjaran Indonesia, 2019)
Since its inception over four decades ago ASEAN has been working towards improving the lives of its citizens. Year 2009 has opened another chapter with the inauguration of AICHR pursuant to Article 14 of the ASEAN Charter at the 15th ASEAN Summit. Ever since, AICHR has conducted various activities. In the midst of these ‘progress’, the vital question remains unanswered; To what extend AICHR has been successful in protecting human rights of citizens in ASEAN countries? This shall be answered through qualitative legal research. This study serves as an analytical basis to predict the future development of the AICHR as well as human rights protection in South East Asia. Furthermore, it contributes to the reform of both ASEAN and AICHR toward implementation of human rights in the region. This research focuses on human rights issues of the Rohingya in Myanmar whereby ASEAN’s policy and action relating to the issue are examined. The finding shows that the policy and action of ASEAN does not provide much support in protecting the rights of the Rohingya. On the contrary, the policy has hindered the effort of AICHR in protecting human rights. AICHR is considered not independent since it almost completely relies on ASEAN. This article thus suggests ASEAN and its member states to take real and concrete measures to protect human rights. In achieving AICHR and ASEAN’s objectives, ASEAN member states must respect human rights and support AICHR with necessary power and measure.